THE SIGNIFICANCE OF FAST DIAGNOSTICS OF SARS-COV-2, GOOD HEALTH CARE ORGANIZATION AND REASONABLE USE OF KNOWLEDGE AND RESOURCES IN THE FIGHT AGAINST COVID-19 - Arsic Arsenijevic, Valentina; Skvarc, Miha (HEALTH CARE, 2020)
In December 2019, a new disease appeared, that is, pneumonia of unknown cause, which was linked to a seafood market in Wuhan (China). Human respiratory epithelial cells were used to isolate a novel coronavirus, named according to the clinical picture “Severe Acute Respiratory Syndrome Coronavirus 2” (SARS-CoV-2), whereas the disease was named the coronavirus disease 2019 (Covid-19). This pandemic has proved to be a great challenge for all professionals dealing with microbiological diagnostics, as well as for all health care workers. The aim of this work is to present the significance of fast diagnostics of SARS-CoV-2, the significance of protection of health of health care workers, and the reasonable use of knowledge and resources in the fight against Covid-19. The previous research has confirmed that in the fight against the SARS-Cov-2 infection, fast diagnostics of SARS-CoV-2, protection of health of health care workers and reasonable use of knowledge and resources during the pandemic are of utmost importance. A special emphasis is put on the vaccination against seasonal influenza, as well as against the invasive pneumococcal disease because, with the help of these vaccines, the diagnosis of Covid-19 could be made easier in the future period, in which the efficient antiviral therapy for SARS-CoV-2 and the vaccine for Covid-19 are expected with great hopes.